2016
DOI: 10.1177/0272989x16662841
|View full text |Cite
|
Sign up to set email alerts
|

Physician Recommendations Trump Patient Preferences in Prostate Cancer Treatment Decisions

Abstract: Objective To assess the influence of patient preferences and urologist recommendations in treatment decisions for clinically localized prostate cancer. Methods We enrolled 257 men with clinically localized prostate cancer (PSA < 20; Gleason 6 or 7) seen by urologists (primarily residents and fellows) in 4 Veterans Affairs Medical Centers. We measured patients’ baseline preferences prior to their urology appointments, including initial treatment preference, cancer-related anxiety, and interest in sex. In long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
108
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 111 publications
(124 citation statements)
references
References 29 publications
(33 reference statements)
14
108
0
Order By: Relevance
“…Furthermore, information about potential interventions was conveyed disproportionately, with providers being much more likely in both cases to explain the benefits of having, rather than not having, the intervention. This would appear in contrast with the finding by Yoon et al in a national survey of obstetricians in which 93% of respondents indicated that a “physician should provide all relevant facts without influencing the patient's decision 1 way or another.” Providers also generally expressed their own recommendations to have the interventions, which in the case of repeat cesarean, was associated with a much greater likelihood of having the intervention, a finding similar to that of Scherr et al concerning provider‐patient interactions about intervention for treatment of prostate cancer. In Diamond‐Brown's series of interviews with obstetricians concerning shared decision‐making, some reported a sense of conflict between their desire to respect patient choice and reliance on their experience and expertise as to the best course of action .…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, information about potential interventions was conveyed disproportionately, with providers being much more likely in both cases to explain the benefits of having, rather than not having, the intervention. This would appear in contrast with the finding by Yoon et al in a national survey of obstetricians in which 93% of respondents indicated that a “physician should provide all relevant facts without influencing the patient's decision 1 way or another.” Providers also generally expressed their own recommendations to have the interventions, which in the case of repeat cesarean, was associated with a much greater likelihood of having the intervention, a finding similar to that of Scherr et al concerning provider‐patient interactions about intervention for treatment of prostate cancer. In Diamond‐Brown's series of interviews with obstetricians concerning shared decision‐making, some reported a sense of conflict between their desire to respect patient choice and reliance on their experience and expertise as to the best course of action .…”
Section: Discussionsupporting
confidence: 55%
“…A study of 167 LPC patients by Sommers et al concluded that it is likely that the association between physician specialty and LPC treatment choice reflects both patient preferences and physician bias toward the treatment options offered by their specialty [35]. Two more recent studies confirmed that physician recommendation influenced treatment choice [36, 37]. In addition, it was found that men expressing a preference for AS were more likely to have received a physician recommendation for AS and less likely to have received a recommendation for active therapy [37].…”
Section: Discussionmentioning
confidence: 99%
“…Studies further indicate that prostate cancer patients are not always presented with all of the treatment options; and the type of treatment recommended depends heavily on the specialty and practice setting of the treating physician (30, 31). One study shows that patients’ treatment choices can actually be predicted by the provider’s recommendation (32). Given these findings, it is not surprising that the recommendations of PTMC providers’ also drive decision-making.…”
Section: Discussionmentioning
confidence: 99%